ANALYSIS OF THE OPTIMAL LOCATION OF TABANAN DISTRICT TO SUPPORT THE DEVELOPMENT OF A FOOD LOGISTIC CENTER - Ocky Soelistyo Pribadi; Adrianto Sugiarto Wiyono; Ni Made Nanda Pradnya Swari; Ni Luh Gede Novi Jayanti; Novan Rachmadi Atmaja (Prosiding Seminar Nasional Manajemen Industri dan Rantai Pasok, 2022)
The development of a Food Logistics Center in Tabanan Regency needs to be supported by determining the optimal location, namely the most accessible area for both achievement and the ease of distributing food products to other locations. For that purpose, the analytical method use in this research is "facility location problem". The results of the analysis regarding to the constraint model, including the distance between the center of the transportation zone in Tabanan Regency, shows that Transportation Zone 7, namely in Samsam Village in Tabanan District, was the optimal location. The total distance traveled between other zone centers to transport zone 7 is 838.8 kilometers, it is the shortest total distance compared to other locations. So, if Food Logistics Center of Tabanan Regency is established in Samsam Village, the transportation for food collecting and distributing will be very efficient.             Keyword : Tabanan Regency, Food Logistics Center, Facility Location Problem, Transpottation Zone, Optimal Location